Sustainable development for rural women artisanal miners in Malawi : obligations under the African Charter and Maputo Protocol - Mkali, Theodora Talumba (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.